2016
DOI: 10.1159/000443448
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Cerebral Infarction in Japanese Hemodialysis Patients: Miyazaki Dialysis Cohort Study (MID study)

Abstract: Background/Aims: Predictors including the preventive effects of antiplatelet and anticoagulant drugs on cerebral infarction (CI) events have not yet been clarified in dialysis patients. The aim of the present study was to examine the risk of CI and preventive effects of these drugs in Japanese hemodialysis patients. Methods: Patients receiving maintenance hemodialysis (n=1,551, median age (interquartile range), 69.0 (59.0-78.0) years; 41.5% female) were enrolled in the Miyazaki Dialysis Cohort Study and prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…One study found the incidence of ischaemic stroke was 10·6% with haemorrhagic type being 2·6% (Wang et al , ). The incidence of stroke in chronic haemodialysis patients has been reported to be 3·78/100 patient‐years (Wiesholzer et al , ) with similar reports in other studies (Findlay et al , ; Shih et al , ; Toida et al , ). In one study 11·6% of patients experienced a stroke and 95% of these were ischaemic.…”
Section: Risk Of Stroke In Patients On Haemodialysissupporting
confidence: 70%
See 1 more Smart Citation
“…One study found the incidence of ischaemic stroke was 10·6% with haemorrhagic type being 2·6% (Wang et al , ). The incidence of stroke in chronic haemodialysis patients has been reported to be 3·78/100 patient‐years (Wiesholzer et al , ) with similar reports in other studies (Findlay et al , ; Shih et al , ; Toida et al , ). In one study 11·6% of patients experienced a stroke and 95% of these were ischaemic.…”
Section: Risk Of Stroke In Patients On Haemodialysissupporting
confidence: 70%
“…However, their findings suggested the magnitude of AF with subsequent stroke in haemodialysis patients was notably less than that reported in the general population. Toida et al () also found similar results, with cerebrovascular infarction events being significantly more common in patients with AF than in those without. The meta‐analyses by Zimmerman et al () found that the stroke rate was increased in patients with AF, at 5·2/100 patient‐years compared with 1·9/100 patient‐years in those without AF.…”
Section: Risk Of Stroke In Patients On Haemodialysismentioning
confidence: 57%
“…In non-hemodialysis patients, the existence of NVAF is a major trigger of cardiac stroke. The hemodialysis patients have multiple high-risk origins of thromboembolic strokes due to systemic atherosclerosis, whereas cardiac stroke is reported to be a major etiology in Japan [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…14 However, the bleeding risk associated with anticoagulation is much higher in the ESRD population than that observed in patients without ESRD 15 and the less frequently acknowledged complications of warfarin are of greater significance in patients with ESRD, specifically accelerated vascular calcification, 16 and calciphylaxis. 17 Reports on the effects of AF are inconsistent - potentially because despite the increasing number of publications examining the factors associated with stroke, 18-33 most fail to address an important issue of survival analysis—the concept of a competing risk. Briefly, a competing risk is an event that occurs during follow-up which forever prevents the event of interest occurring.…”
Section: Introductionmentioning
confidence: 99%